Stimulatory effect of cooling tower biocides on amoebae. - Srikanth, S (1993)
Two species of amoebae were isolated from the cooling tower of an air-conditioning system and examined for effects of exposure to four cooling tower biocides, a thiocarbamate compound, tributyltin neodecanoate mixed with quaternary ammonium compounds, another quaternary ammonium compound alone, and an isothiazolin derivative. The amoebae isolated were Acanthamoeba hatchetti and a Cochliopodium species. Two other amoeba cultures, an A. hatchetti culture and Cochliopodium bilimbosum, were obtained from the American Type Culture Collection (ATCC) and were also tested. The cooling tower isolates were more resistant to most of the biocides than the ATCC isolates were. The isothiazolin derivative was the least inhibitory to all four amoeba isolates, and tributyltin neodecanoate mixed with quaternary ammonium compounds was the most inhibitory to three of the four isolates. After exposure to lower concentrations of the biocides, including for one strain the manufacturer's recommended concentration of one biocide, the cooling tower amoeba populations increased significantly compared with unexposed controls, whereas the ATCC isolates were not stimulated at any of the concentrations tested. In some cases, concentrations which stimulated cooling tower amoebae inhibited the growth of the ATCC isolates. These results suggest that cooling tower amoebae may adapt to biocides, underscoring the need to use freshly isolated cooling tower organisms rather than organisms from culture collections for testing the efficacy of such biocides. The stimulatory effect of biocides on amoeba populations is an alarming observation, since these organisms may be reservoirs for legionellae. Biocides used to control microbial growth may actually enhance populations of host organisms for pathogenic bacteria.